Golovinomyces greeneanus (U. Braun) Heluta (Erysiphales) — новий для України вид борошнисторосяних грибів - Гелюта, В.П.; Коритнянська, В.Г. (Український ботанічний журнал, 2011)
Приведена информация о новом для микофлоры Украины виде мучнисторосяных грибов североамериканского происхождения Golovinomyces greeneanus (U. Braun) Heluta (Erysiphales, Ascomycota). Он обнаружен в 2004 г. на Parietaria ser ica Pancic (Urticaceae) на территории Ботанического сада Одесского национального университета им. И.И. Мечникова. Предполагается, что G. greeneanus, найденный в Северной Америке, Армении и Украине, имеет более широкое распространение, но приводился на растениях семейства Urticaceae как Erysiphe cichoracearum DC. Поэтому соответствующие гербарные образцы нуждаются в критическом пересмотре. Information on Golovinomyces greeneanus (U. Braun) Heluta, a new for Ukraine powdery mildew fungus (Erysiphales, Ascomycota) originally described from North America, is given. The fungus was found in 2004 on Parietaria ser ica Pancic (Urticaceae) in the Botanical Garden of I.I. Mechnikov Odesa National University. Golovinomyces greeneanus, recently reported from USA, Armenia and Ukraine, is supposed to have a wider distribution since it could have been previously recorded on Urticaceae as Erysiphe cichoracearum DC. Thus, a review of those specimens is required.